Constructing a system of integrated management of aviation safety as a key element of airport service quality - Valko, Alla; Soloviova, Olena; Volkovska, Ganna; Herasymenko, Iryna (Eastern-European Journal of Enterprise Technologies, 2021)
The scientific-practical basis of the quality of passenger and clientele service at the airport were studied. This was prompted by the need to determine the role of aviation safety (AS) and its impact on the quality and competitiveness of airport services. It was proved that within the framework of the system, quality monitoring is performed in the areas of the service of aviation safety (SAS). As a result of research, a quantitative assessment of the level of aviation safety of the airport, which is the basis for making a relevant management decision in the analysis subsystems, was determined. Management , in this case, implies the system of measures to improve the activities of the SAS. A procedure for assessing the quality of airport services, which reveals the essence of aviation safety in the system of airport quality management , was devised. The sequence of assessment of the system of aviation safety, reflecting the cost approach, the application of which involves determining the reserves for ensuring aviation safety in the continuous implementation of the quality management system, was proposed. The share of costs of aviation safety (AS) was determined on the example of three airports by economic elements (the model of criteria for choosing a subject) to determine the cost of ensuring an adequate level of aviation safety. It was proposed to introduce a comprehensive indicator of the quality of aviation safety for its functional components, which further makes up the integrated indicator of the quality of provided services. As a result of calculations, the amount of payment for aviation safety using adjustment coefficients to counteract the threat of a possible act of unlawful interference (AUI) will increase. This enables an aircraft company to form timely a reserve to prevent or eliminate the consequences of the AUI by including the aviation safety fee in the total cost of air transport services.